We bury the dead [videorecording (DVD)] - Ridley, Daisy, 1992-; Thwaites, Brenton, 1989-; Smith, Mark Coles, 1987- (Vertical Entertainment, 2026)
After a catastrophic military disaster, the dead don't just rise they hunt. Ava searches for her missing husband, but what she finds is far more terrifying.